Analisis Kinerja Keuangan Pemerintah Kota Jambi Tahun 2020-2024 - Anis Nur Aidah; Mulia Inda Purwati; A. Rozi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the financial performance of the Jambi City Government during the 2020–2024 fiscal period. This research is motivated by the suboptimal management of regional finances, as indicated by revenue realization that has not consistently achieved the targeted amount and the high dependence on transfer funds from the central government. The method used in this study is a qualitative descriptive approach using secondary data in the form of Budget Realization Reports (LRA). The analysis was conducted using financial ratios, including efficiency, effectiveness, growth, and fiscal dependency ratios. The results show that the financial performance of the Jambi City Government during 2020–2024 was generally categorized as fairly good. This is indicated by the efficiency ratio, which ranged from 75% to 79%, and was categorized as efficient, while the effectiveness ratio ranged from 83% to 96%, which was categorized as fairly effective to effective despite annual fluctuations. The regional revenue growth ratio showed a positive trend, with growth values of 8% in 2021, 14% in 2022, 3% in 2023, and 2% in 2024, although growth slowed toward the end of the period. Meanwhile, the fiscal dependency ratio ranged from 73% to 77%, indicating a high level of dependency because the regional government still relied heavily on transfer funds from the central government. Therefore, efforts to optimize Local Own-Source Revenue (PAD) are needed to improve regional fiscal independence.